A Model of Religious Character Education Through Islamic Scouting: Insights from The Hizbul Wathan Scout Movement - Salsabila, Elsa; Fakhruddin, Agus; Komariah, Kokom St. (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2026)
This study aims to describe the implementation of religious values in scouting-based extracurriculars, especially in Hizbul Wathan scouting extracurricular at Junior High School Muhammadiyah 8 Bandung. The research method used is a qualitative-descriptive approach with observation, interview, and document study techniques. The data obtained is then analyzed in three stages: data reduction, data display, and drawing a conclusion. The results of the study show that three main religious values are implemented in the Hizbul Wathan Scouting extracurricular: discipline, morals, and sharia or worship, each of which plays a role in character development, strengthening socio-religious behavior, and strengthening students' religious practices.  These three religious values have a strong foundation in the Qur'an and Sunnah and are integrated into all of Hizbul Wathan's extracurricular activities. The religious values applied in the extracurricular activities of the Hizbul Wathan Scout Movement at Junior High School Muhammadiyah 8 Bandung are concrete efforts by educational institutions to build students' character and achieve the ideal character as a national education goal. Various programs designed to realize these religious values demonstrate the creativity and innovation of educational institutions in making schools centers for character development. The attitude and behavior of students while in the school environment that show a religious character illustrate the success of this program. This research makes a theoretical contribution to the literature of Islamic Religious Education by proposing an integrative model of religious character formation through non-formal Islamic scouting activities. This study provides recommendations for developing scouting extracurricular activities in Muhammadiyah schools as a forum for fostering students' religious character comprehensively.